Modification of titanium alloys surface properties by plasma electrolytic oxidation (PEO) and influence on biological response (2017)
Surface characteristics can mediate biological interaction improving or affecting the tissue integration after implantation of a biomaterial. Features such as topography, wettability, surface energy and chemistry can be key determinants for interactions between cells and materials. Plasma electrolytic oxidation (PEO) is a technique used to control this kind of parameters by the addition of chemical species and the production of different morphologies on the surfaces of titanium and its alloys. With the purpose to improve the biological response, surfaces of c.p titanium and Ti6Al4V were modified by using PEO. Different electrolytes, voltages, current densities and anodizing times were tested in order to obtain surfaces with different characteristics. The obtained materials were characterized by different techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM) and glow discharge optical emission spectroscopy (GDOES). Wettability of the obtained surfaces were measured and the corresponding surface energies were calculated. Superhydrophilic surfaces with contact angles of about 0 degrees were obtained without any other treatment but PEO and this condition in some cases remains stable after several weeks of anodizing; crystal phase composition (anatase-rutile) of the anodic surface appears to be critical for obtaining this property. Finally, in order to verify the biological effect of these surfaces, osteoblast were seeded on the samples. It was found that cell behavior improves as SFE (surface free energy) and coating porosity increases whereas it is affected negatively by roughness. Techniques for surface modification allow changes in the coatings such as surface energy, roughness and porosity. As a consequence of this, biological response can be altered. In this paper, surfaces of c.p Ti and Ti6Al4V were modified by using plasma electrolytic oxidation (PEO) in order to accelerate the cell adhesion process